"Strangers in the House": The Maori Language in Government and the Maori Language in Parliament 1840-1900 - Parkinson, Phil (Victoria University of Wellington Law Review, 2001)
The Treaty of Waitangi conferred upon Her Majesty’s new subjects "all the rights andprivileges of British subjects" and that included, in theory, the right to be represented in the infantgovernment. In practice, however, the right of Maori to vote in elections was not taken seriouslyuntil 1858 and the presence of formally elected members in the House of Representatives was not achieved until August 1868. When they did speak in 1868 the first four Maori members spoke inMaori, and no adequate provision was made for the translation of their words, or for the words ofother members to be translated for them. The proceedings of the House were not printed in Maoriand the Maori members’ speeches were not translated except when it suited the government of theday.Over the next few decades after 1868 there was only an irregular compliance with the standingorders of the House of Representatives and the Legislative Council that Bills and Acts be prepared inboth Maori and English for the better information of "Her Majesty’s subjects of the Native Race".This study traces the extent of the use of the Maori language in the House and in the Council andpoints to a large number of extant Bills and Acts in Maori as well as to the large number whichhave not survived but which are referred to in the New Zealand parliamentary debates. These little-known texts deserve recognition as expressions of legislation in an indigenous tongue reflectingindigenous concerns but they have usually been disregarded in a European-dominated GeneralAssembly.